Assessment of revenue efficiency of Indian scheduled commercial banks. Issue 6 (12th November 2018) - Bhatia, Aparna; Mahendru, Megha
Abstract : Purpose: This paper aims to endeavour to assess revenue efficiency (RE) scores of Scheduled Commercial Banks operating in India. Differences in RE are studied across varying ownership as well. The study also determines the nature of return to scale of Indian SCBs as whole as well as classified across ownership. Number of banks operating as leaders and laggards has also been calculated. Design/methodology/approach: RE of banks is calculated by using the non-parametric approach, namely, data envelopment analysis (DEA). Further, the differences in the efficiency scores are examined by applying Panel Tobit Regression. Findings: The results of DEA suggest that none of the banks has ever achieved full RE score of 1 in any of the years under study. An inconsistent pattern of RE is seen. Private sector banks have performed better than their counterparts in public and foreign sector. Maximum number of banks operating on decreasing return to scale are from public sector, and the highest number of banks operating on constant return to scale belong to Foreign Sector. More number of banks operates as laggards in the Indian financial system. Thus, there still exists room for improvement for banks in all sectors. Originality/value: With specific reference to India, less empirical work has been carried out with respect to RE. As only two studies so far from the literature are available that consider RE exclusively, namely, Ram Mohan and Ray (2004 ) andBhatia and Mahendru (2015 ). However, RamMohan and Ray (2004 ) considered only the reformatory phase, whereasBhatia and Mahendru (2015 ) analyzed the performance for specific points of time only. None of the study has been able to give any concrete findings according to sector-wise performance of banks in terms of RE parameters.